Some Weakly Singular Integral Inequalities and Their Applications to Tempered Fractional Differential Equations - Abdellatif Ben Makhlouf; Djalal Boucenna; A.M. Nagy; Lassaad Mchiri (Journal of Mathematics)
In this paper, we establish several new weakly singular integral inequalities that generalize several previously known ones. Several applications for fractional differential equations in the Caputo context have been derived using tempered fractional differential equations.